SYNERGY BETWEEN EDUCATIONAL TECHNOLOGY AND ISLAMIC RELIGIOUS EDUCATION: EFFORTS TO REALISE CHARACTER-BASED LEARNING, SPIRITUAL VALUES, AND RESPONSIVENESS TO THE CHALLENGES OF THE 21ST CENTURY DIGITAL CIVILISATION - Muhammad Arsyad; Ismaul Fitroh (Indonesian Journal of Education (INJOE), 2025)
This study examines the synergy between educational technology and Islamic Religious Education (IRE) as a strategic effort to realise character-based learning, spiritual values, and responsiveness to the challenges of the 21st-century digital civilisation. Using a descriptive qualitative approach based on literature review, the study analyses the integration of digital platforms such as blended learning, adaptive AI, and Qur'anic-based interactive media in the formation of Islamic character. The main discussion covers the synergy between technology and PAI in strengthening the values of trustworthiness, ihsan, and piety in virtual spaces, as well as implementation and challenges such as the digital divide, negative content distractions, and dehumanisation of interactions, which are overcome through Islamic digital literacy and hybrid spiritual sessions. The results confirm that this synergy produces an adaptive Muslim generation that combines technological skills with akhlakul karimah (good character), becoming the foundation of holistic national education in the Society 5.0 era.